Structural and Functional Characterization of Medicinal Plants as Selective Antibodies towards Therapy of COVID-19 Symptoms - Fatemeh Mollaamin (MDPI AG, 2024)
Considering the COVID-19 pandemic, this research aims to investigate some herbs as probable therapies for this disease. Achillea millefolium (Yarrow), Alkanet, Rumex patientia (Patience dock), Dill, Tarragon, and sweet fennel, including some principal chemical compounds of achillin, alkannin, cuminaldehyde, dillapiole, estragole, and fenchone have been selected. The possible roles of these medicinal plants in COVID-19 treatment have been investigated through quantum sensing methods. The formation of hydrogen bonding between the principal substances selected in anti-COVID natural drugs and Tyr-Met-His (the database amino acids fragment), as the active area of the COVID protein, has been evaluated. The physical and chemical attributes of nuclear magnetic resonance, vibrational frequency, the highest occupied molecular orbital energy and the lowest unoccupied molecular orbital energy, partial charges, and spin density have been investigated using the DFT/TD-DFT method and 6-311+G (2d,p) basis set by the Gaussian 16 revision C.01 program toward the industry of drug design. This research has exhibited that there is relative agreement among the results that these medicinal plants could be efficient against COVID-19 symptoms.
Keywords: dillapiole; alkannin; RC581-607; cuminaldehyde; Article; achillin; natural medication; Immunologic diseases. Allergy; COVID-19 treatment; 15. Life on land; 3. Good health